ANALISIS FRASA ENDOSENTRIS DAN EKSOSENTRIS PADA KORAN DIGITAL DETIK.COM BERJUDUL “KAPOLRI LARANG POLISI TILANG MANUAL” - Ai Risma; Siti Aisyah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
This study aims to describe the use of endocentric and exocentric phrases in the news “Kapolri Larang Polisi Tilang Manual” in the digital newspaper Detik.com October 2022 edition. The descriptions in this study include, patterns and forms of endocentric and excocentric phrases. This research conducts a qualitative descriptive method. The data is gained from the news “Kapolri Larang Polisi Tilang Manual” in the digital newspaper Detik.com October 2022 edition. All of endosentric and excocentric phrases from the news “Kapolri Larang Polisi Tilang Manual” in the digital newspaper Detik.com October 2022 edition were the object this study. The data collection techniques that used in this study are reading and note-taking techniques. The data analysis technique is descriptive analysis technique. The result of this research is that the phrase has various types in it. This study analyzes endocentric and exocentric phrases. The results showed that there were three types of endocentric phrases, namely coordinating endocentric phrases, attributive endocentric phrases and appositive endocentric phrases. The study found two types of exocentric phrases with two types, namely directive exocentric phrases and non-directive exocentric phrases. This research is useful in developing syntactic theory about phrases, especially endocentric and exocentric phrases, and could increase knowledge about types of phrases.